Treatment for Apraxia of Speech in Nonfluent Variant Primary Progressive Aphasia - M. L. Henry; M. V. Meese; S. Truong; M. C. Babiak; B. L. Miller; M. L. Gorno-Tempini (Behavioural Neurology)
There is a growing body of literature examining the utility of behavioral treatment in primary progressive aphasia (PPA). There are, however, no studies exploring treatment approaches to improve speech production in individuals with apraxia of speech (AOS) associated with the nonfluent variant of PPA. The purpose of this study was to examine a novel approach to treatment of AOS in nonfluent PPA. We implemented a treatment method using structured oral reading as a tool for improving production of multisyllabic words in an individual with mild AOS and nonfluent variant PPA. Our participant showed a reduction in speech errors during reading of novel text that was maintained at one year post-treatment. Generalization of improved speech production was observed on repetition of words and sentences and the participant showed stability of speech production over time in connected speech. Results suggest that oral reading treatment may offer an efficient and effective means of addressing multisyllabic word production in AOS associated with nonfluent PPA, with lasting and generalized treatment effects.